Interacting and joint effects of triglyceride-glucose index and hypertension on stroke risk in middle-aged and older Chinese adults: a population-based prospective cohort study - Luo, Yun-Dan; Gan, Ying-Yuan; Liao, Qian; Li, Xu; Huo, Rong-Rui (Frontiers in Cardiovascular Medicine, 2024)
Background: Triglyceride-glucose (TyG) index and hypertension were well-established risk factors for stroke. And TyG index was associated with hypertension. However, no prior study has investigated the interactive effects of the TyG index and hypertension on stroke. This study examined whether hypertension mediates associations of TyG index with incident stroke and the extent of interaction or joint relations of TyG index and hypertension with stroke in middle-aged and older Chinese adults.The China Health and Retirement Longitudinal Study (CHARLS) is an ongoing nationally representative prospective cohort study initiated in 2011. This cohort study included 9,145 middle-aged and older Chinese adults without stroke at baseline. The eposures were TyG index and the logarithmized product of hypertension, as determined during the baseline health examination. The main outcome was self-reported physician-diagnosed stroke which followed up from June 1, 2011, to June 30, 2018.Results: Of the 9,145 participants, 4,251 were men (46.5%); the mean (SD) age was 59.20 (9.33) years. During a median follow-up of 7.1 years, 637 (7.0%) participants developed stroke. In multivariable-adjusted models, the TyG index was significantly associated with the risk of hypertension (odds ratio [OR] per 1-SD increase, 1.29; 95% CI, 1.19-1.41) and stroke (hazard ratio [HR] per 1-SD increase, 1.1816; 95% CI, 1.0302-1.3633). Both multiplicative and additive interactions were observed between TyG index and hypertension on stroke (HR